Atividade leishmanicida e antioxidante das folhas de Krameria tomentosa - MORAES, Waléria Cristina Cardoso de Sousa (2024)
Introduction: Leishmaniasis is a neglected disease caused by protozoa of the genus Leishmania, endemic in many countries. Current treatments have high toxicity and increasing parasite resistance, requiring new, less toxic therapeutic solutions. The objective of this study was to identify the chemical constituents of the extract and fractions of the leaves of Krameria tomentosa A. St.-Hil, as well as to evaluate the cytotoxic effect of the extract and fractions on the promastigotes and amastigotes forms of Krameria tomentosa A. St.-Hil, as well as to evaluate the cytotoxic effect of the extract and fractions of the promastigotes and amastigotes of Krameria tomentosa A. St.-Hil. Leishmanicidal activity (promastigotes and amastigotes), cell death (apoptosis and necrosis), nitric oxide production and antioxidant activity were also evaluated. Statistical analyses were conducted using GraphPad Prism 8.0 (GraphPad Software Inc.). Results: In the analysis of the crude extract (EB) of Krameria tomentosa A.St.-Hil leaves, 18 molecules were identified, most of which were flavonoids. A similar result was observed in the characterization of the ethyl acetate fraction (EAF), in which 8 compounds were identified, all flavonoids. Cytotoxicity against the promastigote forms of L. amazonensis was observed for the in vitro anti-Leishmania activity of the crude extract and fractions of Krameria tomentosa. The selectivity index (SI) was 7.17 for the ethyl acetate fraction in promastigotes and 4.5 for amastigotes. The extract and fractions did not show toxicity in vitro and. Regarding nitric oxide (NO) production, significant induction was observed both by the crude extract and by the ethyl acetate fraction (FAE) compared to the control group. Conclusion: The results of this study indicate that the hydroethanolic extract of Krameria tomentosa leaves has effective leishmanicidal activity against L. amazonensis, especially in the ethyl acetate and hexane fractions, which are rich in flavonoids. In addition, both the crude extract and the ethyl acetate fraction.